2014
DOI: 10.1038/srep04276
|View full text |Cite
|
Sign up to set email alerts
|

Southward spreading of the Fukushima-derived radiocesium across the Kuroshio Extension in the North Pacific

Abstract: The accident of the Fukushima Dai-ichi nuclear power plant in March 2011 released a large amount of radiocesium into the North Pacific Ocean. Vertical distributions of Fukushima-derived radiocesium were measured at stations along the 149°E meridian in the western North Pacific during the winter of 2012. In the subtropical region, to the south of the Kuroshio Extension, we found a subsurface radiocesium maximum at a depth of about 300 m. It is concluded that atmospheric-deposited radiocesium south of the Kurosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
80
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 55 publications
(119 reference statements)
12
80
0
Order By: Relevance
“…Therefore, the amount of 134 Cs in the entire area of the NPSTMW would be estimated as 11 ± 1.7 PBq. Kumamoto et al ( 2014 ) reported 134 Cs in the area around the center of the NPSTMW during January and February 2012, estimating the total inventory of 134 Cs in the NPSTMW to be 6 PBq. These estimates may indicate that 6 PBq of 134 Cs intruded into the NPSTMW during March and April 2011, as observed in January and February 2012 (Kumamoto et al 2014 ), and 3.3-6.7 PBq additional 134 Cs had intruded into the NPSTMW during the 2011-2012 winter season, observed in September 2012 (this study).…”
Section: Amount Of 134 Cs In Subsurface Core Waters In the Southern Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the amount of 134 Cs in the entire area of the NPSTMW would be estimated as 11 ± 1.7 PBq. Kumamoto et al ( 2014 ) reported 134 Cs in the area around the center of the NPSTMW during January and February 2012, estimating the total inventory of 134 Cs in the NPSTMW to be 6 PBq. These estimates may indicate that 6 PBq of 134 Cs intruded into the NPSTMW during March and April 2011, as observed in January and February 2012 (Kumamoto et al 2014 ), and 3.3-6.7 PBq additional 134 Cs had intruded into the NPSTMW during the 2011-2012 winter season, observed in September 2012 (this study).…”
Section: Amount Of 134 Cs In Subsurface Core Waters In the Southern Areamentioning
confidence: 99%
“…Kumamoto et al ( 2014 ) reported 134 Cs in the area around the center of the NPSTMW during January and February 2012, estimating the total inventory of 134 Cs in the NPSTMW to be 6 PBq. These estimates may indicate that 6 PBq of 134 Cs intruded into the NPSTMW during March and April 2011, as observed in January and February 2012 (Kumamoto et al 2014 ), and 3.3-6.7 PBq additional 134 Cs had intruded into the NPSTMW during the 2011-2012 winter season, observed in September 2012 (this study). Because the vertical resolution of this study was low (seven layers between the surface and 1,000 m), and the study area was limited to the western part of the NPSTMW, considerable uncertainty should have been taken into account.…”
Section: Amount Of 134 Cs In Subsurface Core Waters In the Southern Areamentioning
confidence: 99%
“…Radionuclides were released from the FNPP through two major pathways: direct discharges of radioactive water and atmospheric deposition onto the North Pacific Ocean. Indirect estimation of that deposition is in the range 6.4-35 PBq (Kumamoto et al, 2014). The total amount of 137 Cs isotope released into the ocean was estimated to be 3.6±0.7 PBq by the end of May 2011 .…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is supported by an increased concentration of radiocesium measured in its core at station C43 by Kaeriyama et al (2013) at the end of July 2011. The Kumamoto et al, 2014) with measured radiocesium concentrations at the background level (the green diamonds) and with higher concentration levels (the magenta diamonds). (b-d) The Lagrangian maps show evolution of the Tsugaru eddy (TsE), which originated on 4 February 2012 (a) after splitting of the HE and was sampled by Budyansky et al (2015) at station 84 on 5 July 2012 and shown to have increased radiocesium concentrations (the magenta diamond in d).…”
Section: The Hokkaido Eddymentioning
confidence: 99%
See 1 more Smart Citation